Analisis Struktur Cluster Pasar Industri pada Sektor Publik - Muhammad Yasin; Azizatun Fitriani; M. Ibrahim Baihaqi (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to analyze the structure of industrial market clusters in the context of the public sector. The industrial market cluster structure refers to the pattern of relationships between companies in a sector that are interrelated in the aspects of production, distribution and marketing. This research uses a primary and secondary data analysis approach to identify patterns and relationships between entities in the public sector. Through the use of cluster analysis methods, this research describes the relationship between companies in the public sector based on characteristics such as industry specialization, geographic location, and marketing networks. The results of this analysis can provide valuable insights for policy makers and stakeholders in understanding the dynamics of industrial markets in the public sector as well as the potential for collaboration and competition between industry players.